Idiom variants and synonymous idioms in English and Vietnamese: The similarities and differences - Giang, Dang Nguyen (VNU Journal of Foreign Studies, 2011)
Abstract. Idioms in both English and Vietnamese are regarded as special language units because they usually have their own typical fixed properties. However, in fact, we can see a lot of idioms violating the principles of these fixed properties. They are idiom variants and synonymous idioms. This article is about their signs and forms as well as the similarities and differences between English and Vietnamese in terms of these.Key words: idiom variants, synonymous idioms, forms, language units, fixed properties.